2020
DOI: 10.6007/ijarbss/v10-i2/6927
|View full text |Cite
|
Sign up to set email alerts
|

Vernacular Architecture in Old Malay Building through Malay Historiography

Abstract: Vernacular is said to be derived from the Latin term vernaculus which means domestic or local which means 'place'. However, in this context, the vernacular traditions clearly emphasize the conditions, local materials, environment and behavior as well as local customs that focus on traditional Malay society. This is reflected in the architecture that can be studied with the senses dependent on the thoughts and views of the community. Among them is the architecture of old Malay building. Research vernacular aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…The term 'naga berjuang' is personified as powerful and mystical creatures with benevolent and malevolent attributes. This characterization is consistent with the findings of Badaruddin et al (2020) and Jaffar et al (2017). The term 'naga' has its etymological origins in the Malay word for 'dragon' and is frequently used in Southeast Asian literature to describe mythical beings imbued with celestial power (Eslit, 2023).…”
Section: Naga Berjuang (Fighting Dragon)supporting
confidence: 86%
See 1 more Smart Citation
“…The term 'naga berjuang' is personified as powerful and mystical creatures with benevolent and malevolent attributes. This characterization is consistent with the findings of Badaruddin et al (2020) and Jaffar et al (2017). The term 'naga' has its etymological origins in the Malay word for 'dragon' and is frequently used in Southeast Asian literature to describe mythical beings imbued with celestial power (Eslit, 2023).…”
Section: Naga Berjuang (Fighting Dragon)supporting
confidence: 86%
“…Norhaiza added that the concept of the naga berjuang is dragons symmetrically facing each other, even though it does not form the real shape of a dragon. Previous researchers, such as Badaruddin et al (2020) and Jaffar et al (2017), have discussed the naga motif in Malay society and culture, as indicated in Table 4, emphasizing its symbolism of strength and power. However, with the arrival of Islam in the 14th century, the transformation of the naga motif has evolved over time due to the avoidance of figurative elements, a phenomenon supported by the study conducted by Sanusi and Legino (2015).…”
Section: Fauna Motifmentioning
confidence: 99%
“…The Kulim tree (Scorodocarpus borneensis) could easily be found in the Malay peninsula and is especially suitable for constructing buildings due to its hardness, heaviness, durability, fine texture, resistance to insects, and strong wooden fibres (Dumanauw, 2001: 22-23). Clearly, the ready availability and characteristics of the Kulim tree wood made it a natural choice as one of the best construction materials for traditional Malay cities (Jaffar et al, 2020). Sometimes, these materials are used in combination with each other in order to produce stronger and more varied buildings.…”
Section: Literature Reviewmentioning
confidence: 99%